How Non-CS preservice teachers conceptualize and engage with computational thinking through 3D game design: Insights from an XR-enhanced maker experience - Tugce Aldemir; Jewoong Moon; Ali Bicer; Gyuri Byun; Carlos Manrique Perez; Vivek Sabanwar (Computers & Education: X Reality)
This study explored how low-threshold, XR-enhanced maker environments can support preservice teachers’ (PSTs) engagement with computational thinking (CT) practices and perceptions. Using a scaffolded, three-week module built around Roblox Studio, non–computer science PSTs engaged in iterative game design activities progressing from paper prototypes to storyboard rule maps and interactive 3D builds. Findings suggest that design tasks encouraged shifts from surface-level CT definitions to more applied reasoning, particularly in decomposition and algorithmic thinking during storyboard development. However, participants encountered new challenges during 3D implementation, including spatial logic demands and limited debugging fluency. Reflections highlighted frequent micro-debug cycles and collaboration as key supports, even when such processes were not fully visible in final artifacts. While many PSTs remained hesitant about coding, most recognized transferable skills—such as perseverance, creativity, and empathy—as relevant to their future teaching. These results highlight the promise and complexity of XR maker spaces as a bridge between conceptual CT understanding and authentic classroom application. Implications include the need for scaffolded supports targeting spatial reasoning, rule-system translation, and reflective design dispositions in CT-focused teacher education.